Students’ Motivation in Learning English - Yulfi Yulfi; Ahwalusah Aalayina (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine students' motivation in learning English and its effect on their English learning achievement. The research method used is survey research with a quantitative approach. Data were collected using questionnaires, interviews, and documentation. The questionnaire was adapted from the Attitude Motivation Test Battery (AMTB) designed by Gardner. The results showed that 52% of students took an active role in learning English. Students are relative